Anxiety and mood regulating treatment for adult attention deficit disorder - Maszaidi Z,; Hatta Sidi,; Nurul Hazwani H, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Anxiety and mood symptoms are common in Attention Deficit Disorder. We highlight a case of 23-year-old man who presented with poor attention and gradual poor academic performance. His poor academic achievement was noted by the parent, only for the past 2-3 yrs prior to the psychiatric consultation. He developed low mood but there was no biological symptoms of depression. He was started on both daily treatment of Buproprion 150 mg daily, and Ritalin 10 mg PRN basis. The common treatment for attention deficit disorder in was a stimulant but in this case an antidepressant was used. It was shown that patient started to show improvement with treatment and was able to focus on his study.